Public Relations Management In An Effort To Improve Public Services On The Website Of The Information And Documentation Management Officer Of Central Bengkulu - Putra, Dirgantara; Sari, Sapta; Maryaningsih, Maryaningsih (Harmonization : Jurnal Ilmu Sosial, Ilmu Hukum, dan Ilmu Ekonomi, 2024)
Public service encompasses activities to fulfill the basic needs of citizens according to their rights, as mandated by the 1945 Constitution. The Central Bengkulu Social Service established the Information Technology Public Relations section, referred to as Public Relations DinSos Central Bengkulu, to accommodate public complaints through their official website. Based on Law No. 14 of 2008 on Public Information Disclosure, this service aims to ensure open information for the public and improve the governance of public institutions. However, responses to public complaints are still minimal and often slow, due to mechanisms that do not yet follow procedures and the unresponsiveness of regional work units (SKPD). This study aims to analyze public relations management in efforts to improve public services at the Central Bengkulu PPID using the public relations management theory by Cutlip, Scoot M., Center, Allen H., and Broom. This research uses a qualitative descriptive method with data collection techniques through observation, interviews, and documentation. The results show that the Central Bengkulu Social Service has taken various steps to improve public services, including upgrading technology infrastructure, training officers, and updating operational procedures. However, improvements are still needed in response speed and information transparency. Overall, this study reveals that although significant efforts have been made, there is still room for improvement, particularly in more intensive two-way communication and increasing service access in remote areas. These improvement efforts are expected to enhance public satisfaction and trust in the provided public services